POLITIK SIKLUS ANGGARAN LOKAL (STUDI APBD KOTA SURAKARTA MENJELANG PILKADA 2010) - HARSASTO, PRIYATNO (Politika: Jurnal Ilmu Politik, 2014)
Incumbent always has a strategic position in general election. Many literatures discuss how incumbents take advantage of his position by holding on his budgeting power to create personal popularityr. In political economic literature this phenomena is called politics budget cycle. This research trys to uncover the practice of this kind of politics in Surakarta: wheater the incumbent used his budgeting power to win the local election or not?In doing so, this research used descriptive analisys which took advantage of documents as well as indepth interview. The main finding of this research is we cannot find any evidence of the use of politics budget cycle in Surakarta.Two sensitive sectors, namely social sectors did not increase dramatically before the election. When probing into some important sections of the budget, it is found that alocation for education and health services increase dramatically. However, those two sections are parts of basic services so that we cannot conclude that it has something to do with incumbent’s political ambition to retain his power. When we look into education and health programs, we found that those programs have already served the need of the people long before the election. In conclusion, there are not any clue that incumbent take advantage of his budgetary power to win his position as mayor of Surakarta.